The mind's mirror : risk and reward in the age of AI - Rus, Daniela; Mone, Gregory (W. W. Norton & Company, 2024)
"An exciting introduction to the true potential of AI from the director of MIT's Computer Science and Artificial Intelligence Laboratory. Imagine a technology capable of discovering new drugs in days instead of years, helping scientists map distant galaxies and decode the language of whales, and aiding the rest of us in mundane daily tasks, from drafting email responses to preparing dinner. Now consider that this same technology poses risks to our jobs and society as a whole. Artificial Intelligence is no longer science fiction; it is upending our world today"--Jacket.